Anatomics: High-throughput phenotyping of plant anatomy - Strock, Christopher F.; Schneider, Hannah M.; Lynch, Jonathan P. (Trends in plant science, 2022)
Anatomics is a novel phenotyping strategy focused on high-throughput imaging and quantification of plant anatomy from field-grown plants. Here we highlight its potential applications for genetic and physiological analysis of plant anatomical phenotypes.